THE ROLE OF EDUCATIONAL PSYCHOLOGY IN IMPROVING THE EFFECTIVENESS OF THE LEARNING PROCESS - M Azka; Risfa Tri Ulfa; Salis Masruhi; Afriana Santosa (Journal of Educational Review and Research, 2026)
Educational psychology plays an important role in understanding students’ learning processes and improving the effectiveness of learning in educational settings. This study aims to analyze the role of educational psychology in enhancing learning effectiveness through a review of relevant literature. The research employs a qualitative approach using the systematic literature review (SLR) method. Data were collected from several scientific databases, including Scopus, Web of Science, ERIC, DOAJ, Google Scholar, as well as national journal portals such as SINTA and Garuda. Through the processes of identification, screening, and eligibility evaluation, 22 relevant articles were selected for analysis. The data were analyzed using qualitative descriptive techniques through literature organization, concept categorization, and synthesis of research findings. The results indicate that educational psychology significantly contributes to learning effectiveness through factors such as learning motivation, student engagement, self-regulated learning, teacher–student interaction, teacher efficacy, and a conducive learning environment. These findings suggest that integrating educational psychology principles into teaching practices can support the development of adaptive instructional strategies, increase students’ active participation, and create more effective learning environments.